The performance of warm mix asphalt incorporating asphalt binder improved with amine nano-tio2 additives - Buhari, Rosnawati (2022)
Warm mix asphalts (WMAs) are a green technology that requires low energy consumption and is more environmentally friendly than conventional hot mix asphalt (HMA) technologies. However, there are some drawbacks that cause WMAs to be less frequently adopted. As such, further research is warranted. To that end, this study examined the possibility of modifying asphalt binders with nano-TiO2 (titanium dioxide nanoparticles) for use in WMAs. Initially, a PG70 asphalt binder was modified with 9.0% nano-TiO2 to meet the performance requirements of a PG76 asphalt binder. As the viscosity of the 9% nano-TiO2 modified asphalt binder was marginally higher than that of unmodified PG70 asphalt binders, the 9.0% nano-TiO2 was further modified by its total weight with 5.0%, 5.5%, 6.0%, and 6.5% octadecylamine (OCTA) and 3.5%, 4.0%, 4.5%, and 5.0% 3- aminopropyltriethoxysilane (TRI) to produce new nanoparticle additives namely amine nano-TiO2 OCTA (TIOCTA1, TIOCTA2, TIOCTA3, and TIOCTA4) and amine nano-TiO2 TRI (TIOTRI1, TIOTRI2, TIOTRI3, and TIOTRI4). These new nanoparticle additives were then added to PG70 asphalt binders to improve the workability of asphalt mixtures at lower temperatures. After mixed, the asphalt binders were then evaluated in terms of storage stability as well as physical, rheological, and morphological characteristics. Then, the asphalt mixtures incorporating these asphalt binders were compacted using temperatures that were 20°C to 40°C lower than that required by HMA to produce WMAs. The performance of all samples was evaluated in terms of resistance to rutting, fatigue, and moistureinduced damage via a resilient modulus test, indirect tensile fatigue (ITF) test, dynamic creep (DC) test, and a modified Lottman test. The test results indicated that the performance of the modified asphalt binders had improved to PG76 asphalt binder, homogeneous, stable in storage, and had a high modulus. Furthermore, all TIOCTA and TIOTRI asphalt mixtures that had been produced at lower temperatures were more resistant to fatigue, rutting, and moisture-induced damage than those of HMA. A comparative study also concluded that the TIOTRI3 asphalt mixture compacted at 30°C lower than the HMA, had significantly better resistance to rutting, fatigue and moisture-induced damage.